2005
DOI: 10.1097/00004356-200503000-00005
|View full text |Cite
|
Sign up to set email alerts
|

Disability pension despite vocational rehabilitation? A study from six social insurance offices of a county

Abstract: Many long-term sick-listed individuals move from vocational rehabilitation to pension, rather than reaching the goal of return to work. There is thus reason to consider whether rehabilitation resources are being used optimally. Individuals receiving disability pensions are consuming financial and personnel resources at the insurance offices and also consume a large amount of health care. The general objective of the study was to evaluate the proportion of individuals granted vocational rehabilitation but then … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0
1

Year Published

2006
2006
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 0 publications
1
10
0
1
Order By: Relevance
“…For review question 2 on the differential outcomes of vocational rehabilitation, five observational studies over time [19,[23][24][25][26] of people who had been on long-term sick leave were included. The study samples were drawn from official, population-based or employee-based registers of sick-listed individuals, which recorded who received vocational rehabilitation and who returned to work, and were analysed in terms of the characteristics of the people more or less likely to return to work afterwards.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…For review question 2 on the differential outcomes of vocational rehabilitation, five observational studies over time [19,[23][24][25][26] of people who had been on long-term sick leave were included. The study samples were drawn from official, population-based or employee-based registers of sick-listed individuals, which recorded who received vocational rehabilitation and who returned to work, and were analysed in terms of the characteristics of the people more or less likely to return to work afterwards.…”
Section: Resultsmentioning
confidence: 99%
“…This allows considerable differences in the choice of rehabilitation measure in different offices and in treatment and/or options offered to a person on sick leave [12,17].…”
Section: The National Policy Contextmentioning
confidence: 99%
See 1 more Smart Citation
“…Wallman et al16 found that the number of annual days of SA had the best prognostic precision for DP compared with other predictors such as age, length of education, and geographical area. Several other studies have also found that previous SA increases the risk of long-term SA and DP 11,1721…”
Section: Introductionmentioning
confidence: 81%
“…Rehabilitation measures are often transformed into DP [13]. In a 2 year follow-up of people receiving rehabilitation, 46% ended up with a DP [14]. In a 3 year followup study, data showed that psychosocial stress preceding rehabilitation increased the risk of a DP by fourfold for women, but for men the difference was less prominent and not significant [15].…”
Section: Introductionmentioning
confidence: 99%